1996
DOI: 10.1093/ajcn/64.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Feeding formula without arachidonic acid and docosahexaenoic acid has no effect on preferential looking acuity or recognition memory in healthy full-term infants at 9 mo of age

Abstract: Preferential looking acuity and novelty preference (a test of recognition memory) were determined by using Teller Acuity Cards and the Fagan Test of Infant Intelligence, respectively, for 399-433 healthy full-term infants at 39 +/- 1 wk of age. Duration of breast-feeding and age of infant at introduction and amount and type of formula were determined by questionnaire. Seventy-four infants (17%) were never breast-fed; another 92 infants (21%) were still receiving breast milk as the milk source at 39 wk of age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 40 publications
4
34
1
1
Order By: Relevance
“…Visual acuity was measured using both the acuity card procedure and a visual evoked potential method and no differences were observed between the different groups at the ages of 2, 4, 6, 9 and 12 months. Our ®ndings agree with both Innis et al (1994Innis et al ( , 1996Innis et al ( , 1997 and Auestad et al (1997). In their recent study, Birch et al (1998) also found no effect of diet on visual acuity, as measured with the forced choice looking protocol, at different time points during the ®rst 12 months of life.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Visual acuity was measured using both the acuity card procedure and a visual evoked potential method and no differences were observed between the different groups at the ages of 2, 4, 6, 9 and 12 months. Our ®ndings agree with both Innis et al (1994Innis et al ( , 1996Innis et al ( , 1997 and Auestad et al (1997). In their recent study, Birch et al (1998) also found no effect of diet on visual acuity, as measured with the forced choice looking protocol, at different time points during the ®rst 12 months of life.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to human milk, most arti®cial formulas do not contain n-6 LCP and n-3 LCP to supply the infant with AA and DHA. The present study, like other studies (Innis, 1992;Innis et al, 1997;Jùrgensen et al, 1996;Uauy et al, 1992), showed that the concentrations of 22 : 6n-3 and other essential fatty acids were lower in plasma and red blood cells of formula-fed infants compared with those of breastfed infants, whereas fatty acids of the n-7 and n-9 family were higher. These differences were more pronounced in the subgroup of infants who received human milk until 7 months of age as compared with the total group of breastfed infants (mean duration of breastfeeding : 16 weeks).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In these infants, formulas enriched with DHA were found to improve visual acuity and neuro-mental development. These effects disappeared at somewhat later age (Carlson et al, 1993;Innis et al, 1996), but were of longer duration in other studies . An increased occurrence of sepsis or necrotising enterocolitis at enteral feeding with supplemented marine n-3 PUFA cannot be ruled out (Carlson et al, 1996).…”
Section: Human Experiments With N-3 Pufamentioning
confidence: 49%